Anticancer Properties of Essential Oils and Other Natural Products. (25th March 2018) - Blowman, K.; Magalhães, M.; Lemos, M. F. L.; Cabral, C.; Pires, I. M.
Abstract : Essential oils are secondary metabolites with a key-role in plants protection, consisting primarily of terpenes with a volatile nature and a diverse array of chemical structures. Essential oils exhibit a wide range of bioactivities, especially antimicrobial activity, and have long been utilized for treating various human ailments and diseases. Cancer cell prevention and cytotoxicity are exhibited through a wide range of mechanisms of action, with more recent research focusing on synergistic and antagonistic activity between specific essential oils major and minor components. Essential oils have been shown to possess cancer cell targeting activity and are able to increase the efficacy of commonly used chemotherapy drugs including paclitaxel and docetaxel, having also shown proimmune functions when administered to the cancer patient. The present review represents a state-of-the-art review of the research behind the application of EOs as anticancer agents both in vitro and in vivo . Cancer cell target specificity and the use of EOs in combination with conventional chemotherapeutic strategies are also explored.